Differential Dermatologic Adverse Events Associated With Checkpoint Inhibitor Monotherapy and Combination Therapy: A Meta-Analysis of Randomized Control Trials - Ge, Yang; Zhang, Huiyun; Weygant, Nathaniel; Yao, Jiannan (Frontiers in Pharmacology, 2021)
Abstract Background: As immune checkpoint inhibitors (ICIs) transition to the forefront of cancer treatment, a better understanding of immune related adverse events (IRAEs) is essential to promote safe clinical practice. Dermatologic adverse events are the most common IRAEs and can lead to drug withdrawal and decreased quality of life. This meta-analysis aimed to investigate the risk of the most prevalent dermatologic adverse events (pruritus and rash) among various ICI treatment regimens. Methods: A systematic search of electronic databases was performed to identify qualified randomized controlled trials (RCTs). Data for any grade and high grade pruritus and rash were extracted for meta-analysis. Two reviewers independently assessed methodological quality. The relative risk summary and 95% confidence interval were calculated. Results: 50 RCTs involving 29941 patients were analyzed. The risk of pruritus (2.15 and 4.21 relative risk respectively) and rash (1.61 and 3.89 relative risk respectively) developing from CTLA-4 or PD-1/-L1 inhibitor were increased compared to placebo, but this effect was not dose-dependent. PD-1/-L1 plus CTLA-4 inhibitor was associated with increased risk of pruritus (1.76 and 0.98 relative risk respectively) and rash (1.72 and 1.37 relative risk respectively) compared to either monotherapy. Compared with CTLA-4 inhibitor, PD-1/-L1 inhibitor had a significantly decreased risk of pruritus and rash in both monotherapy and combination therapy (0.65 and 0.29 relative risk respectively). No significant difference was found between PD-1/-L1 inhibitor combined with chemotherapy and PD-1/-L1 monotherapy in any grade and high grade rash (0.84 and 1.43 relative risk respectively). In subgroup analyses, PD-1 inhibitor was associated with reduced risk of pruritus and rash compared to PD-L1 inhibitor. Conclusions: Our meta-analysis demonstrates a better safety profile for PD-1/-L1 inhibitor compared to CTLA-4 inhibitor in terms of pruritus and rash among both monotherapy and multiple combination therapies. PD-L1 inhibitor may contribute to an increased risk of pruritus and rash compared to PD-1 inhibitor.